Female labor supply: Why is the US falling behind? - Francine D. Blau; Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2013)
In 1990, the US had the sixth highest female labor participation rate among 22 OECD countries. By 2010, its rank had fallen to 17th. We find that the expansion of family-friendly policies including parental leave and part-time work entitlements in other OECD countries explains 28-29% of the decrease in US women's labor force participation relative to these other countries. However, these policies also appear to encourage part-time work and employment in lower level positions: US women are more likely than women in other countries to have full time jobs and to work as managers or professionals.
Keywords: J16; J22; 330; gender; labor supply